Analysis of the Properties of Vacancy Mediated Methyl Ammonium Lead Iodide Perovskite: A DFT Based Study - Md. Abdullah Al Asad; Md. Abdul Alim; Mst. Halima Khatun; Abinash Chandro Sarker; Md. Arifur Rahman (East European Journal of Physics, 2025)
Intrinsic defects have a significant impact on carrier transport properties of Methyl Ammonium Lead Iodide (MAPI) Perovskite CH3NH3PbI3. In this paper, we investigated how lead vacancies affect the photovoltaic properties of MAPI using density functional theory (DFT) studies. Lead vacancies in perovskite materials can significantly impact carrier dynamics and device efficiency. Our findings indicate that the lower energy configuration of the Pb vacancy does not create deep trap states that would otherwise reduce carrier lifetime. This suggests that Pb vacancies in MAPI might not be as detrimental to carrier dynamics as previously thought. Pb vacancies could potentially be compensated by other defects or dopants in the material, which might mitigate their negative effects on carrier dynamics. The introduction of a Pb vacancy leads to additional electronic states near the conduction band minimum (CBM) within the fundamental band gap. This indicates that the vacancy introduces localized electronic states that influence carrier behavior. The Highest Occupied Molecular Orbital (HOMO) becomes more localized around the vacant area, while the Least Unoccupied Molecular Orbitals (LUMOs) are only partially localized. This localization around the vacancy does not create strong trapping states that could hinder carrier movement. The presence of vacancies causes atomic movements that result in a more distorted optimized structure. This structural distortion can influence the overall material properties and potentially impact device performance. The HOMO and LUMO levels are primarily derived from the p orbitals of the atoms involved. This highlights the importance of p orbital interactions in determining the electronic properties of the material